2015
DOI: 10.1002/jnr.23636
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem/progenitor cell‐laden microfibers promote transplant survival in a mouse transected spinal cord injury model

Abstract: Previous studies have demonstrated that transplantation of neural stem/progenitor cells (NS/PCs) into the lesioned spinal cord can promote functional recovery following incomplete spinal cord injury (SCI) in animal models. However, this strategy is insufficient following complete SCI because of the gap at the lesion epicenter. To obtain functional recovery in a mouse model of complete SCI, this study uses a novel collagen-based microfiber as a scaffold for engrafted NS/PCs. We hypothesized that the NS/PC-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
(57 reference statements)
1
30
1
Order By: Relevance
“…NSPCs are capable of differentiating into three main CNS cell types: neurons, astrocytes, and oligodendrocytes. Readers are referred to an extensive review of preclinical transplantation studies for spinal cord regeneration [57,[60][61][62]. However, there are numerous challenges ahead before cell therapy can be translated into a clinical testing.…”
Section: Cns Injuriesmentioning
confidence: 99%
“…NSPCs are capable of differentiating into three main CNS cell types: neurons, astrocytes, and oligodendrocytes. Readers are referred to an extensive review of preclinical transplantation studies for spinal cord regeneration [57,[60][61][62]. However, there are numerous challenges ahead before cell therapy can be translated into a clinical testing.…”
Section: Cns Injuriesmentioning
confidence: 99%
“…Besides the absence of spontaneous recovery in untreated animals, some authors failed to observe functional motor recovery in injured rodents treated with scaffold-based strategy. 28,36,37 In all abovementioned studies a segment resection model was utilized. It was suggested that the absence of recovery of hindlimbs function in animals subjected to complete spinal cord transection was likely due to insufficient axon regeneration and integration in functional circuit.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23,37,38] We used three types of neural cells to fabricate microfiber-shaped neural tissues: primary mouse neural stem cells (mNSCs) dissected from the midbrain of mice (mNSC units), primary cortical cells (cortical units), and primary hippocampal cells (hippocampal units). To prepare the rod-shaped neural units in an accurate and reproducible manner, we developed a fiber-cutting device that can fix the microfiber-shaped neural tissues in a culture In the brain, 3D neural networks such as the hippocampalprefrontal pathway, [1,2] amygdala pathway, [3][4][5] and visual pathway [3,6,7] comprise various independent regions that are connected by aligned nerve fibers.…”
Section: Rod-shaped Neural Units For Aligned 3d Neural Network Connecmentioning
confidence: 99%